The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/00914037.2010.483217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polyaniline:TiO2Nanocomposites

Abstract: Thin films of polyaniline (PANi) and PANi:titanium oxide (TiO 2 ) composites have been synthesized by sol-gel spin coating technique. The TiO 2 powder of particle size 50-60 nm was synthesized by sol-gel technique and the polyaniline was synthesized by chemical oxidative polymerization of aniline. The composite films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) Fourier transform infrared (FTIR) and UV-vis spectroscopy, and the results were compared with polyaniline films. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…It has specifically been observed that the size of dispersed particles plays a significant role in controlling the physical= electrochemical properties of Composite Polymer Electrolytes (CPE) [1][2][3][4][5][6] . Transition metal oxides such as copper oxide, iron oxide, nickel oxide and zinc oxide nanoparticles have special physicochemical properties and high specific surface area, which may be different from their atomic or bulk counterparts [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…It has specifically been observed that the size of dispersed particles plays a significant role in controlling the physical= electrochemical properties of Composite Polymer Electrolytes (CPE) [1][2][3][4][5][6] . Transition metal oxides such as copper oxide, iron oxide, nickel oxide and zinc oxide nanoparticles have special physicochemical properties and high specific surface area, which may be different from their atomic or bulk counterparts [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, on the basis of conducting polymers and inorganic 29 nanoparticles, the nanocomposites have attracted attention as it 30 seems to be the potential route to improve the performance of 31 materials in devices. Several reports on the synthesis of the 32 nanocomposites of polyaniline with Fe 3 O 4 [15], ZnO [16], ZrO 2 [17], 33 TiO 2 [18] and montmorillonite [19] nanoparticles have already 34 been published. 35 Titanium carbide (TiC) is one of the most important metal 36 carbides with excellent properties, such as high melting tempera- 37 ture, hardness, strength, wear, corrosion resistance, electrical 38 conductivity, and thermal conductivity [20,21].…”
mentioning
confidence: 99%
“…In addition, the structure looks more porous. Figure. 1 demonstrate the morphology of polyaniline undoped (EB) powder prepared at 0 o C. It can be seen that the polyaniline particles are highly micro-porous type morphology and able to increase the liquid-solid interfacial region [12][13][14]. The exceedingly porosity nature of the polymer materials and the massed circular morphology was affirmed with a FESEM study.…”
Section: Resultsmentioning
confidence: 77%